Implementación de la contabilidad comercial y su incidencia financiera en la empresa Dicoceramica del Canton Machala, provincia de el Oro, periodo noviembre y diciembre del 2015. - Valarezo Jaramillo, Karem Betzabeth (2017)
The thesis entitled is a contribution to the development of commercial activities, which will deepen in the financial and institutional growth it also will allow to implement all the knowledge acquired during the career of Accounting and Auditing at the National University of Loja. Its implementation helps to comply with the objectives set for this project; It began with the design of the Plan and Accounting Manual, raised according to the requirements of the business, then the initial inventory was taken, showing the values of the assets and liabilities that were found at the beginning of the fiscal year; subsequently, and based on source documents obtained during the corresponding Memorandum of operations it is performed, allowing the development of the Daybook, the General Ledger, Trial Balance, Worksheet, and finally the financial statements and accounting annexes; process that safely provide henceforth real and timely information to the business. At the end of the present research findings among the main is the implementation of the accounting system as a tool to control operations and a recommendation for the immediate implementation of an accounting process to obtain accurate and timely information of accounting activities were obtained in Dicocerámica likewise representing an alternative solution for the improvement and development of it.